Translation and Validation of the Arabic Version of the Cancer Needs Questionnaire-Short Form - Loai Abu Sharour (Elsevier, 2021)
Objective: Care needs among Arabic cancer patients have not been assessed previously due to the lack of translated instrument that can determine the care needs among the cancer patients in Arab countries. The aim of this study was to translate and validate an Arabic version of the Cancer Needs Questionnaire-Short Form (CNQ-SF). Methods: A cross-cultural adaptation and psychometric testing was used. Brislin's model of translation was used to translate the CNQ-SF from English to Arabic. A cross-cultural adaptation and psychometric testing was used. A sample of 113 participants with different types of cancer completed the study surveys including the CNQ-SF (Arabic version) and Functional Assessment of Cancer Therapy-General (FACT-G). Descriptive, bivariate statistics and exploratory factor analysis (EFA) were performed. Results: Content validity was evaluated by a panel of experts and 20 participants and showed that translated scale was clear, understandable, and logical in order. Reliability analysis of CNQ-SF domains ranged from 0.85 to 0.93 and 0.94 for the total Arabic version of CNQ-SF. Convergent analysis showed a significant relationship between CNQ-SF (Arabic version) and FACT-G. Results of EFA indicated that the CNQ-SF scale has 32-items. It consists of five domains, the results indicated that Kaiser-Meyer-Olkin was 0.851, and Bartlett's Test of Sphericity was significant (significant (P < 0.001). Conclusions: The current study indicates that the Arabic version of CNQ-SF is valid, reliable, and applicable. It can be used by researchers, clinical practitioners, and health educators in Arab countries.